Interreligious Harmony : A Case Study Kapuas Intefaith Harmony Forum Kapuas Regency and Ma’na Cum Maghza Approach - Ushansyah, Ushansyah; Taufiq, Muhammad; Anwar, Khairil (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
This study aims to examine the relevance of interpreting QS. Āli ʿImrān [3]:118–119 in fostering interreligious harmony within the pluralistic society of Kapuas Regency, which is currently experiencing local social and political dynamics, by employing the hermeneutical approach of Ma’na Cum Maghza developed by Sahiron Syamsuddin. This approach is selected for its capacity to integrate the historical-textual meaning of Qur’anic verses with their universal ethical messages in contemporary contexts. Methodologically, this research adopts a qualitative-interpretative design through library research and field studies. Data sources include Qur’anic verses, classical and modern Qur’anic commentaries, academic literature on Islamic hermeneutics and interreligious relations, as well as documents and social practices related to the role of the Interfaith Harmony Forum (FKUB) of Kapuas Regency. Data analysis is conducted by identifying the ma’na (original meaning) of the verses within their socio-historical context, followed by an exploration of their maghza (contextual significance) for present-day realities. The findings reveal that QS. Āli ʿImrān [3]:118–119, which was originally revealed in a context of political vigilance toward non-Muslims during the aftermath of the Battle of Uhud, can be reinterpreted through the Ma’na Cum Maghza approach as conveying broader socio-ethical messages that emphasize prudence, openness, and moral responsibility in interreligious interactions. Values such as at-tasamuh (tolerance), at-taʿāwun (cooperation), and at-tarāḥum (compassion) emerge as universal ethical principles that resonate with the initiatives and practices of FKUB Kapuas in maintaining social cohesion amid local political polarization. The implications of this study affirm that the Ma’na Cum Maghza approach positions the Qur’an as a source of universal ethics that promotes a peaceful and inclusive Islam, while also offering an applicable model for strengthening synergy among FKUB, the Ministry of Religious Affairs, and the Kapuas Regency Government based on Qur’anic values and local cultural wisdom. Penelitian ini bertujuan untuk mengkaji relevansi penafsiran QS. Ali Imran [3]:118–119 dalam membangun harmoni antarumat beragama di tengah masyarakat majemuk Kabupaten Kapuas yang tengah menghadapi dinamika sosial dan politik lokal, dengan menggunakan pendekatan hermeneutis Ma’na Cum Maghza sebagaimana dikembangkan oleh Sahiron Syamsuddin. Pendekatan ini dipilih karena kemampuannya mengintegrasikan makna historis-tekstual ayat dengan pesan etis universal yang kontekstual. Secara metodologis, penelitian ini menggunakan desain kualitatif-interpretatif melalui studi pustaka dan studi lapangan. Sumber data meliputi ayat-ayat Al-Qur’an, karya tafsir klasik dan modern, literatur akademik tentang hermeneutika Islam dan relasi antaragama, serta dokumen dan praktik sosial yang berkaitan dengan peran Forum Kerukunan Umat Beragama (FKUB) Kabupaten Kapuas. Analisis data dilakukan dengan menelusuri ma’na (makna asal) ayat dalam konteks sosio-historisnya, kemudian mengelaborasi maghza (signifikansi) ayat bagi konteks kekinian. Hasil penelitian menunjukkan bahwa QS. Ali Imran [3]:118–119 yang pada mulanya diturunkan dalam konteks kewaspadaan politik terhadap kelompok non-Muslim pada masa Perang Uhud, melalui pendekatan Ma’na Cum Maghza dapat ditafsirkan ulang sebagai pesan sosial-etis yang lebih luas, yang menekankan prinsip kehati-hatian, keterbukaan, dan tanggung jawab moral dalam interaksi antarumat beragama. Nilai-nilai at-tasamuh (toleransi), at-ta‘awun (kerja sama), dan at-tarahum (kasih sayang) muncul sebagai prinsip etis universal yang selaras dengan praktik dan program FKUB Kapuas dalam menjaga kohesi sosial di tengah potensi polarisasi politik. Implikasi penelitian ini menegaskan bahwa pendekatan Ma’na Cum Maghza menempatkan Al-Qur’an sebagai sumber etika universal yang mendorong lahirnya Islam yang damai dan inklusif, sekaligus menawarkan model aplikatif bagi penguatan sinergi antara FKUB, Kementerian Agama, dan Pemerintah Kabupaten Kapuas berbasis nilai-nilai Qur’ani dan kearifan budaya lokal.